Towards a General Development Strategy in The Developing Economy : (With Focus on the Iraqi Economy) - Hoshiar Marouf (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The developing economies focused their production and export activities on a few primary materials. In economies that concentrate their exports on crude oil, such as the Iraqi economy, these economies suffer from general structural distortions and are constantly subject to severe fluctuations in the values of their total exports, and then in their other economic indicators, especially trade balance, balance of payments, the state’s public budget, as well as the growth rates of investment, national income and employment. Thus, the relationship between the external sector and the domestic economy has become complicated, and numerous challenges have emerged for the development, especially the overall, processes, which require the identification of the main factors for the strategic transformation of the national economy as a whole.